2015
DOI: 10.1016/j.bbamcr.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial autophagy: Origins, significance, and role of BNIP3 and NIX

Abstract: Mitochondrial autophagy (mitophagy) is a core cellular activity. In this review, we consider mitophagy and related cellular processes and discuss their significance for human disease. Strong parallels exist between mitophagy and xenophagy employed in host defense. These mechanisms converge on receptors in the innate immune system in clinically relevant scenarios. Mitophagy is part of a cellular quality control mechanism, which is implicated in degenerative disease, especially neurodegenerative disease. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
201
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(208 citation statements)
references
References 122 publications
3
201
0
4
Order By: Relevance
“…In cells treated with pathogen-associated molecular patterns (DAMPs) mitochondrial dysfunction has been observed, as well as the increase in ROS synthesis. These events activate mitochondrial permeability transition, which causes the leakage of mtDNA to the cytosol (Oka et al, 2012;Ney, 2015). Sun et al (2013) reported that mitochondrial DAMPs induce changes in endothelial permeability, suggesting that release of mitochondrial factors from dead or dying cells can be a critical factor in the early endothelial response to damage.…”
Section: Perspectivementioning
confidence: 99%
“…In cells treated with pathogen-associated molecular patterns (DAMPs) mitochondrial dysfunction has been observed, as well as the increase in ROS synthesis. These events activate mitochondrial permeability transition, which causes the leakage of mtDNA to the cytosol (Oka et al, 2012;Ney, 2015). Sun et al (2013) reported that mitochondrial DAMPs induce changes in endothelial permeability, suggesting that release of mitochondrial factors from dead or dying cells can be a critical factor in the early endothelial response to damage.…”
Section: Perspectivementioning
confidence: 99%
“…Both Bnip3 and Nix are primarily localized on the outer mitochondrial membrane, and share a similar mechanism to induce mitophagy (for reviews, see [80,81] ). The difference between the two proteins during the induction of mitophagy is of interest.…”
Section: Bnip3-and Nix/bnip3l-mediated Mitophagymentioning
confidence: 99%
“…Bnip3 has been reported to participate in hypoxia-induced mitophagy in rat heart. Nix was fi rst found to be essential for the induction of mitophagy during the maturation of red blood cells [79] .Both Bnip3 and Nix are primarily localized on the outer mitochondrial membrane, and share a similar mechanism to induce mitophagy (for reviews, see [80,81] ). The difference between the two proteins during the induction of mitophagy is of interest.…”
mentioning
confidence: 99%
“…Since mitophagy in yeast involves the interaction between cytosolic Atg11 and mitochondrial Atg32 (Kanki et al, 2015), and since the Htt C-terminal can interact with mammalian Atg32 homologues (BNIP3 and NIX), mammalian mitophagy is proposed to involve Htt-BNIP3/NIX interactions (Ochaba et al, 2014). Significantly, BNIP3 and NIX also interact with autophagosomal LC3, and while the BNIP3/NIX-associated mitophagy pathway has been primarily associated with reticulocyte maturation (Ney, 2015), recent evidence implicates this pathway in neuronal mitophagy (Shi et al, 2014). Thus, wild-type Htt may have a role in mitophagy that is disturbed by mHtt, nevertheless, whether and how N-terminal polyQ disturbs the interaction of the C-terminal with mitochondria remains undetermined.…”
Section: Mitophagy and Huntingtin Proteostasismentioning
confidence: 99%